Education-based incarceration and recidivism : the ultimate social justice crime-fighting tool - Fitch, Brian D.; Normore, Anthony H. (Educational leadership for social justice., 2012)
Education-Based Incarceration and Recidivism: The Ultimate Social Justice Crime Fighting Tool takes a penetrating look at the needs and challenges of society's disenfranchised jail populations. It is incumbent to encourage public awareness of the causes that underlie the destructive cycles plaguing these populations, including the abuse and neglect that cycle through generations. When effectively addressed through education the economic burden on society is lightened and an advocacy to increase understanding engenders a humane response. When connecting education-based incarceration to leadership and social justice, several issues come to mind, beginning with the universal understanding that definitions of social justice are based on a variety of factors, like political orientation, religious background, and political and social philosophy. An increased body of researchers in educational leadership, ethics, law, sociology, corrections, law enforcement, criminal justice, and public health agree that social justice is concerned with equal justice, not just in the courts, but in all aspects of society. Social justice demands that people promote a just society where people have equal rights and opportunities; everyone, from the poorest person on the margins of society to the wealthiest deserves an even playing field.The intended audience for this book includes academics, national and international law enforcement agencies, and correctional institutions interested in establishing and assessing the effectiveness of an education-based incarceration program. This book can be used by educators and students interested in studying organizational leadership, correctional theory, recidivism, social and restorative justice, and education-based incarceration.